(untitled) (Sains Humanika, 2021)
The purpose of this study is to identify the relationship between transformational leadership style and self-efficacy among leaders. Eighty leaders at a government agency in Johor Bahru were involved as the respondents. Quantitative methods were used for this study by using a set of 25-item questionnaires on transformational leadership style and self-efficacy. The Multifactor Leadership Questionnaire (MLQ) founded by Bass and Avolio (1992) was used to measure the transformational leadership styles, while the self-efficacy scale developed by Chen, Gully and Eden (2001) were used to measure the respondents’ self-efficacy. Data were analysed using descriptive statistics and inferences by using the Statistical Package for Social Science (SPSS) version 21. Overall, the results showed that the transformational leadership style among the respondent is at moderate level. The findings also showed that the respondents’ self-efficacy level is high. Meanwhile, the Pearson Correlation analysis showed that there is a moderate and positive relationship between the transformational leadership style and leader’s self-efficacy. In conclusion, it was found that the transformational leadership style is related to leader’s self-efficacy. This findings from this research can be used as an empirical support for future studies in the leadership and self-efficacy field among leaders in government agencies di Malaysia.